IMPACT OF RISK OF LOSS AND HARVEST AREA ON PADDY PRODUCTION IN JENEPONTO REGENCY - Noer Ibrah Ibrahim; Ratnawati Tahir; Irma Sribianti; Akhmad; Sri Mardiyati (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
The planting area, harvested area, production, and productivity of lowland rice have continued to be increased to support rice self-sufficiency in Indonesia. Rice is a strategic commodity because it is a staple food in Indonesia. This study aims to analyze the trend of harvested area, crop failed harvest, production, productivity, and production risk as well as the effect of harvested area and risk of loss (failed harvest) on lowland rice production in Jeneponto Regency. The type of data is secondary data of annual time series for the last 20 years (2005-2024), sourced from the Central Statistics Agency and the Department of Agriculture. The data analysis used trend analysis, coefficient of variation, and linear regression. The results of this study indicate that lowland rice farming in Jeneponto Regency during the last 20 years (2005-2024) experienced an increasing trend in harvested area of ​​893.82 hectares/year, crop failure area increased by 63.28 hectares/year, production increased by 4,839 tons/year, and productivity only increased by 0.0061 tons/ha/year. The average risk of lowland rice production is 35.09 percent, and the average area of ​​crop failure is 99.32 hectares. The harvested area has a positive and significant effect on lowland rice production, if the harvested area is increased by one hectare, rice production will increase by 5.28 tons. The area of ​​crop failure has a negative and significant effect on lowland rice production, if the area of ​​crop failure is increased by one hectare, rice production will decrease by 6.22 tons. Risk management is important to be carried out so that the risk of loss can be minimized, so that production and productivity continue to increase sustainably.